Deciphering the rule of antigen-antibody amino acid interaction - Jiang, Min; Fang, Changyin; Ma, Yongping (Frontiers in Immunology, 2023)
Antigenic drift is the biggest challenge for mutagenic RNA virus vaccine development.The primary purpose is to determine the IEMM (immune escape mutation map) of 20 amino acids replacement to reveal the rule of the viral immune escape.To determine the relationship between epitope mutation and immune escape, we use universal protein tags as a linear epitope model. To describe and draw amino acid linkage diagrams, mutations of protein tags are classified into four categories: IEM (immune escape mutation), ADERM (antibody-dependent enhancement risk mutation), EQM (equivalent mutation), and IVM (invalid mutation). To overcome the data limitation, a general antigenantibody(Ag-Ab) interaction map was constructed by analyzing the published three-dimensional (3D) Ag-Ab interaction patterns.Most amino acid replacements are IVM and EQM. (iii) Once aromatic amino acids replace nonaromatic amino acids, the mutation is often IEM. (iv) Substituting residues with the same physical and chemical properties easily lead to IEM. Therefore, this study had important theoretical significance for future research on antigenic drift, antibody rescue and vaccine renewal design.The antigenic epitope mutations were typed into IEM, ADERM, EQM, and IVM types to describe and quantify the results of antigenic mutations. The antigen-antibody interaction rule was summarized as one-to-many interaction rule. To sum up, the epitope mutation rules were defined as IVM and EQM predomination rule, and aryl mutation escape rule.